2020
DOI: 10.1186/s13059-020-1947-1
|View full text |Cite|
|
Sign up to set email alerts
|

Assembly of hundreds of novel bacterial genomes from the chicken caecum

Abstract: Background: Chickens are a highly important source of protein for a large proportion of the human population. The caecal microbiota plays a crucial role in chicken nutrition through the production of short-chain fatty acids, nitrogen recycling, and amino acid production. In this study, we sequence DNA from caecal content samples taken from 24 chickens belonging to either a fast or a slower growing breed consuming either a vegetable-only diet or a diet containing fish meal. Results: We utilise 1.6 T of Illumina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 95 publications
6
104
1
Order By: Relevance
“…Only two species appeared to be restricted (at ≥1x coverage) to just a single sample: Aliarcobacter thereius and Candidatus Avibacteroides faecavium. Correlation clustering con rmed structure in the data linked to BioProject ( Figure S2b) -for example, the BioProject from the study by Glendenning et al [15] clearly shows enhancement of clostridial species compared to other BioProjects, re ected samples sourced from chicks with no post-hatching contact with an adult bird.…”
Section: Distribution Of Microbial Speciesmentioning
confidence: 70%
See 3 more Smart Citations
“…Only two species appeared to be restricted (at ≥1x coverage) to just a single sample: Aliarcobacter thereius and Candidatus Avibacteroides faecavium. Correlation clustering con rmed structure in the data linked to BioProject ( Figure S2b) -for example, the BioProject from the study by Glendenning et al [15] clearly shows enhancement of clostridial species compared to other BioProjects, re ected samples sourced from chicks with no post-hatching contact with an adult bird.…”
Section: Distribution Of Microbial Speciesmentioning
confidence: 70%
“…We performed a search of PubMed with the species name and "chicken", leaving aside the 33 species named by Glendenning et al [15]. This suggested that our study provides the rst-evidence-in-chickens for the majority (81/125) of these species (Table S14).…”
Section: Remarkable Microbial Genome Diversity In the Chicken Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomics is a powerful tool which allows us to examine the entire genetic repertoire of the rumen microbiota without the need for culturing. Our group has previously published thousands of metagenome assembled genomes from cattle rumen samples (19, 20) and hundreds of genomes from chicken caecal samples (21), many of which were identified as novel species.…”
Section: Introductionmentioning
confidence: 99%